Subclavian artery pseudoaneurysm in Behcet's disease - Yildirim, Ahmet; Isik, Ahmet; Koca, Suleyman (Springer London Ltd, 2007)
Behcet's disease (BD) is an autoimmune, multisystemic, and chronic inflammatory disease. Although it affects all systems, involvement of the vascular system is of vital importance. Pseudoaneurysm ruptures in the arteries are the major causes of sudden deaths in BD. Although pseudoaneurysms in aorta and pulmonary arteries are rare, it is even more rare in the subclavian arteries. In our case, a pulsatile mass in the right clavicular area was determined to be associated with BD and this case is presented because subclavian artery pseudoaneurysm is seen rarely in BD.
5th Congress of the African-League-Against-Rheumatism -- FEB 18-22, 2007 -- Nairobi, KENYA
Keywords: Behcet disease; subclavian artery pseudoaneurysm